2009
DOI: 10.1039/b819080a
|View full text |Cite
|
Sign up to set email alerts
|

An integrated hybrid interference and absorption filter for fluorescence detection in lab-on-a-chip devices

Abstract: We present a hybrid optical filter design that combines interference and absorbing components for enhanced fluorescence detection in miniaturized highly-integrated lab-on-a-chip devices. The filter is designed in such a way that the advantages of each technology are used to offset the disadvantages of the other. The filter is fabricated with microfabrication compatible processes and materials for monolithic integration with microelectronics and microfluidics devices. The particular embodiment of the filter des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 13 publications
0
49
0
Order By: Relevance
“…In waveguidebased optical sensors, it has been demonstrated that a high refractive index superstrate layer on the waveguide surface results in lower limits of detection [6,7]. In integrated optical devices, multilayer thin films with high refractive index contrast are extensively used for the fabrication of optical interference filters and mirrors [8,9]. In addition to high refractive index, important requirements for high refractive index materials include high optical quality and transparency over the visible spectral range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In waveguidebased optical sensors, it has been demonstrated that a high refractive index superstrate layer on the waveguide surface results in lower limits of detection [6,7]. In integrated optical devices, multilayer thin films with high refractive index contrast are extensively used for the fabrication of optical interference filters and mirrors [8,9]. In addition to high refractive index, important requirements for high refractive index materials include high optical quality and transparency over the visible spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high refractive index, important requirements for high refractive index materials include high optical quality and transparency over the visible spectral range. Film thickness control is also critical and the optimum thickness depends on the refractive index value and is usually between 30 and 150 nm [6][7][8][9]. Furthermore, a low temperature deposition process is frequently desirable to facilitate the integration of different optical components on substrates such as glass or plastic.…”
Section: Introductionmentioning
confidence: 99%
“…A significant limitation of the current design is lack of optical filters in the probe tip. The LODs reported here could be improved by integrating optical filters directly onto the tips of the fibers, thus reducing fluorescence background due to light scattering that occurs along the fiber length [5557]. Nevertheless, our probes have the advantage of focusing into small channels (down to 15 µm deep × 50 µm wide), enabling their use for a variety of applications, such as electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…Despite several advantages of this filtering solution (single layer, low cost, simple integration into a-Si:H photodetectors) they are inefficient when excitation and emission wavelengths are in close proximity as in the case of small Stokes' shift fluorophores (Δλ < 50 nm). Other solutions based on interference filters exhibit higher filtering efficiencies but require a large number of layer pairs (up to 20) to be deposited and for each layer its thickness to be tuned accurately [15,16].…”
Section: Introductionmentioning
confidence: 99%